THE ROLE OF JAVANESE TRADITIONAL GAMES IN IMPROVING CHILDREN’S SOCIAL BEHAVIOR - Mahardika, Esti Kurniawati (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
Traditional games are increasingly losing place in children’s hearts as information-technology advances. Children prefer modern online-based games that can be accessed at any time via gadgets. Although some online games provide a chat feature that allows communication between users (children), children still cannot make direct contact. This study aims to determine the effectiveness of using traditional games in improving children’s social behavior. This study uses an experimental design method. Researchers compared the scores of children’s social behavior before and after participating in traditional Javanese games. The research was conducted at Mojoranu I Kindergarten, Bojonegoro. Data were collected by means of observation using research instruments for 19 days of observation. Then, to analyze the data, the researchers use data triangulation involving the results of observation scores, interviews and documentation. The results showed that the average score of children’s social behavior before playing Javanese traditional games was 20.83 while the average score after playing Javanese traditional games was 39.11. Based on the results of this study, it can be said that traditional Javanese games are effective in improving children’s social behavior. Parents and/or teachers can use traditional games as a tool to improve children's social skills.